DECREASE IN PRODUCTION AND QUALITY OF GRAIN DUE TO NECK BLAST DISEASE IN SOME LOWLAND RICE VARIETIES - Subiadi, Subiadi; sipi, Surianto; Basundari, Fransiska Renita Anon (Universitas Lampung, 2019)
Decrease in production and quality of grain due to neck blast disease in some lowland rice varieties. Neck blast disease of rice causes a decrease in yields both in quantity and quality. The study was conducted to see the effect of neck blast disease on the characteristics of grain and yields of several high yielding varieties of lowland rice. The varieties used were Ciherang, Inpari 4, Inpari 7, Inpari 8, and Inpari 9. The parameters observed were the incidence and severity of neck blast disease, the ratio of the size of the seeds of healthy and sick panicles and the estimated production. The analysis showed that all varieties planted were infected by neck blast disease, but based on Disease Incident rate in the Necks, Ciherang and Inpari 8 varieties reacted susceptible to neck blast disease, Inpari 7 and 9 were moderate and Inpari 4 was resistant to neck blast disease. The quality of panicle grain infected by neck blast disease has decreased the size of grain width and was significantly different from grain of healthy panicles in all varieties. The highest estimated productivity was Inpari 4 variety of 10,378 kg/ha which experienced a decrease in production by 35.86% and the lowest was Ciherang variety of 8,367 kg/ha which experienced a decrease in production by 48.37% when they were infected by neck blast disease.